Efeitos de nanopartículas magnéticas sobre a microalga Raphidocelis subcapitata - Melo, Daniela Correia de (2016)
Nanotechnology has developed rapidly in recent decades, characterized as the fourth industrial revolution. In the current market, the use of products that incorporate nanotechnology is ascending. The nanoparticles (NPs) are characterized as materials with 1 to 100 nm at leat one of its dimension, which have large surface area and physicochemical properties distinct from their source material. In particular, the magnetic nanoparticles are of great interest in materials science, and their applications is investigated in biotechnology / biomedicine, magnetic resonance imaging, data storage, catalysis, environmental remediation process and others. However, the risks of the development of new nanomaterials for the environment are still underexplored and research that regulate its use is still incipient. Thus, this study aimed to evaluate the effects of magnetic nanoparticles into one kind of freshwater phytoplankton, the microalgae Raphidocelis subcapitata. NPs used were Fe3O4 NPs (magnetite); Cu-Fe2O4 NPs (hematite with adsorbed copper) and CoFe2O4 NPs (cobalt ferrite). Besides traditionally used parameters in aquatic ecotoxicology as cell density and chlorophyll a content, were also evaluated the biochemical composition (protein, lipids and carbohydrates) of this microalgae, fluorescence parameters of chlorophyll a and oxidative stress induced by the production of reactive oxygen species (ROS). Our studies indicate that only high concentrations, higher than 50 mg L-1, of magnetic nanoparticles modified the physiologic response of microalgae, in which case increased concentrations of lipids and proteins. The chlorophyll fluorescence parameters and oxidative stress induced by ROS in general were sensitive to NPs, particularly in higher concentrations. Therefore, the implementation and use of magnetic and bimetallic NPs in aquatic environments can be considered safe for chloroficea Raphidocelis subcapitata since in low concentrations.